Ellipsometry Principles and Techniques for Materials Characterization - Wahaia, Faustino (IntechOpen, 2017)
Ellipsometry is rapidly emerging as a popular solution addressed to new materials science challenges and technological pitfalls hindering its effective application on modern problems. Amid the nowadays active development of materials of top notch, ellipsometry is also evolving rapidly both in the academic and industry sectors. The global industry strategies, introduce the latest scientific advances at manufacturing new, more accurate, and reliable ellipsometry systems to tackle emerging challenges. The book provides a comprehensive overview on the principles and technical capabilities of the modern ellipsometry highlighting its versatility in materials characterization.